Reproductive biology of the southern thorny skate Amblyraja doellojuradoi (Chondrichthyes, Rajidae) - Delpiani, Gabriela Elina (2016)
The total lengths (LT) of 193 males (209-556mm) and 130 females (275-515mm) of Amblyraja doellojuradoi, a commercial by-catch species on the Argentinean continental shelf, which are increasingly retained, were analysed. No sexual dimorphism was observed in the LT at which 50% of individuals were sexually mature; males matured at 448mm and females at 411mm, c. 80 and 82% of maximum LT. The hepato-somatic index was similar among sexes, but significantly different between maturity stages, being lower in mature than immature specimens. Males had no seasonal difference in the hepato-somatic index and females had the lowest index in autumn. The gonado-somatic index was lower in males than in females and significantly higher in mature than immature specimens of both sexes. Males had the highest index in autumn and females had no seasonal difference. Collectively, these results would indicate that A. doellojuradoi breeds in autumn.